2018
DOI: 10.1007/s00439-018-1910-3
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease

Abstract: With the recent advance in genome-wide association studies (GWAS), disease-associated single nucleotide polymorphisms (SNPs) and copy number variants (CNVs) have been extensively reported. Accordingly, the issue of incorrect identification of recombination events that can induce the misannotation of multi-allelic or hemizygous variants has received more attention. However, the potential distorted calculation bias or significance of a detected association in a GWAS that may result due to the coexistence of CNVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 91 publications
(106 reference statements)
4
43
0
Order By: Relevance
“…The heterozygous variant (c.1133G>A, p.Arg378His) identified in the Hispanic patient was defined as rare by a minor allele frequency <0.001 in reference databases, and was predicted to be tolerated (CADD = 9.618, SIFT prediction as tolerated, GERP++ = 2.23). The novel variant (c.418C>T, p.Leu140Phe) identified in the Egyptian patient was predicted to be damaging/likely damaging (CADD = 20.5, SIFT prediction as deleterious, GERP++ = 6.04) and was interpreted to be in the homozygous state and not an “apparent homozygous allele/haplotype” versus a hemizygous state due to 16p11.2 deletion (Liu et al, ; Tables and S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterozygous variant (c.1133G>A, p.Arg378His) identified in the Hispanic patient was defined as rare by a minor allele frequency <0.001 in reference databases, and was predicted to be tolerated (CADD = 9.618, SIFT prediction as tolerated, GERP++ = 2.23). The novel variant (c.418C>T, p.Leu140Phe) identified in the Egyptian patient was predicted to be damaging/likely damaging (CADD = 20.5, SIFT prediction as deleterious, GERP++ = 6.04) and was interpreted to be in the homozygous state and not an “apparent homozygous allele/haplotype” versus a hemizygous state due to 16p11.2 deletion (Liu et al, ; Tables and S1).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in TBX6 encoding the T‐box 6 transcription factor, a key regulator of the segmental patterning of the paraxial mesoderm, have been implicated in CS (Chapman & Papaioannou, ; P. H. White, Farkas, McFadden, & Chapman, ). We previously reported that a rare heterozygous loss‐of‐function (LoF) TBX6 allele (i.e., a deletion copy number variant [CNV] or a stop gain/frameshift variant allele) in trans with a hypomorphic common variant TBX6 haplotype (T‐C‐A composed of three SNPs, rs2289292–rs3809624–rs3809627; Liu et al, ; Wu et al, ) could explain about 10% of CS cases in the Chinese Han population (Wu et al, ). We use the term “ TBX6 compound inheritance model” to refer to this pattern of TBX6 bi‐allelic variation.…”
Section: Introductionmentioning
confidence: 99%
“…The left ten genes, which were novel findings of TWAS, also had known associations with many cognitive and mental health traits. For example, previous GWAS reported that HCK was associated with chronotype 82 , LGALS3 with schizophrenia 83 , UBE2C with reaction time 75 , KLRD1 with adolescent idiopathic scoliosis 84 , OSER1 with cognitive performance 77 and Alzheimer’s disease 76 , and PRPF3 with chronotype 76,85 and neuropsychiatric disorders 86 . In summary, TWAS novel and validated genes expand the overview of gene-level pleiotropy across these traits, suggesting that neuroimaging-derived biomarkers could be useful in studying a wide range of complex traits.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 genes, 7 ( OSER1, TREH, PRPF3, KLRD1, TGM7, DCTPP1, UBE2C ) were validated in one or more of the five validation datasets and were discussed in previous section. For the other 6 genes ( CELSR3, MYO9A, DNAJC24, GYPE, TMEM136, MOB4 ) genes, MOB4 was reported for major depression 94 and autism spectrum disorder/schizophrenia 95 , DNAJC24 was linked to adolescent idiopathic scoliosis 84 , and CELSR3 was associated with education 65 and cognitive ability 64,81 . The same checking was then performed for the 308 significant gene-trait associations of brain tissue-specific TWAS.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies have demonstrated that mutations in PIK3CA are su cient to induce oncogenic transformation in chicken embryo broblasts through enhancement lipid kinase activity and activation of mTOR and AKT1 signaling [15]. However, all seven variants were absent from the Deciphering Disorders Involving Scoliosis and COmorbidities (DISCO, http://discostudy.org/) study composed of 4000 exome sequencing data of the Chinese population [16][17][18]. PIK3CA p.Glu453Lys, p.Glu542Lys, p.Gln546Lys and p.His1047Tyr were absent from the Genome Aggregation Database (gnomAD, https://gnomad.broadinstitute.org).…”
Section: Genetic Characteristicsmentioning
confidence: 99%